Determining the damping factor of sedimentary rocks required for seismically designed structures - Worthington, M; King, MS; Marsden, JR (2001)
Relationships for the shear damping ratio Ds (a function of shear quality factor Qs) and modulus decay curve Gseis/Gmax as a function of shear strain for mudrocks have been developed. Field experiments to determine damping ratio and elastic moduli should be performed at frequencies as close as possible to the bandwidth (0-100 Hz) of interest for building design. Estimates of these parameters made from extrapolating laboratory core (MHz) or wireline (kHz) data to lower frequencies can be highly unreliable. Field estimates of damping ratio are very dependent on, and often totally dominated by, the effects of scattering of P and S waves by inhomogeneities in the rock mass structure. This is, particularly, the case when open fractures or cracks are present in near-surface rocks. © 2001 Elsevier Science Ltd. All rights reserved.